Digital analysis and development of ride-through capability of ac contactor with respect to voltage sag characteristics - Ismail, N.A.; Kasim, L.M.; Mokhtar, N.F.; Yaakub, T.S.T.; Mokhlis, Hazlie (IEEE, 2010)
This paper presents the development of digital simulator tool for sensitivity analysis of ac contactor with respect to voltage sag characteristics. The simulator tool allows varying of the sag characteristics for the purpose of evaluating the behavior of ac contactor under very worst conditions of voltage sags. Describing voltage sag characteristics by their magnitude and duration only without consideration of other parameters is no longer suitable to fully assess the equipments sensitivity. Therefore, this paper presents the necessity to include the point-on-wave of sag initiation and phase shift of sag to explain the sensitivity of ac contactor during sags. From the simulation results, the ride through capability curve is constructed to identify ac contactor sensitivity levels. The curve has demonstrated a rather complex behavior of the ac contactor. By having a simulator tool, ac contactor analysis can be simulated for any type of configurations without having to perform laboratory experiments.